Synopsis: Improving agricultural value chain coordination and gender inclusiveness in Papua New Guinea - Kosec, Katrina; Schmidt, Emily; Carrillo, Lucia; Fang, Peixun; Ivekolia, Mark; Ovah, Raywin (International Food Policy Research Institute, 2022)
Maximizing efficiency throughout the entire agri-food value chain is critical to fostering greater economic growth and poverty reduction in Papua New Guinea (PNG). Investments in midstream value chain infrastructure (e.g., improved storage facilities, rural feeder roads, electricity, and cold storage transport) are crucial to strengthen linkages between producers and consumers. These investments should also promote inclusive development that benefits both men and women value chain actors. In this study, we analyzed three key value chains in Papua New Guinea—poultry, sweet potato, and fresh vegetables—aiming to guide policymakers and stakeholders toward ways to improve productivity, increase revenue, and bolster competitiveness and inclusiveness within the agriculture and livestock sectors.